Model Pelayanan Sosial Yayasan Panti Asuhan Menara Kasih Indonesia dalam Mewujudkan Kesejahteraan Anak - Regita Cahyani Adiningsih; Aprida Simamora; Anna Chirsty Br Ginting Manik; Lovi Dwita; Hairani Siregar (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Children are the next generation and the hope for the nation's future. However, not all children have the opportunity to grow up in a complete and supportive family environment. The Menara Kasih Indonesia Orphanage Foundation serves as a social solution for children who have lost their parents or are in a state of neglect. This research aims to examine how the background, social services, and caregiving patterns are implemented in this orphanage. The methods used were literature study, descriptive qualitative with observation, and direct interviews with the orphanage administrators and one of the children from the orphanage. The research results show that this orphanage applies a warm and supportive familial parenting style, where the staff actively play the role not only as parental substitutes but also as companions in the children's learning process. The caretakers help the children with their schoolwork and provide emotional support. However, in terms of funding and facilities, the Menara Kasih Indonesia Orphanage Foundation still has limitations.